Pengaruh Return on Asset (ROA), Debt to Equity Ratio (DER) Dan Current Ratio (CR) Terhadap Harga Saham (Studi Empiris Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this study is to analyze and find out whether there are positive and negative influence Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR) over stock prices. The population is registered food and beverage companies and still registered in (BEI) for period 2016-2018. The sample in this study included 13 companies. The data analysis method uses a multiple linier regresion model. The result of this study indicate that (1) ROA has a significant positive effect on the stock price of food and beverage (2) DER has insignificant negative effect on the stock prices of food and beverage, and (3) CR has insignificant negative effect on the stock prices of food and beverage.Keywords: Return on Assets, Debt to Equity Ratio,Current Ratio, and Stock Price